(−)-Epicatechin and the colonic metabolite 2, 3-dihydroxybenzoic acid protect against high glucose and lipopolysaccharide-induced inflammation in renal proximal tubular cells through NOX-4/p38 signalling. Issue 10 (22nd September 2020) - Álvarez Cilleros, David; López-Oliva, María Elvira; Martín, María Ángeles; Ramos, Sonia
Abstract : Chronic hyperglycaemia and inflammation are present in diabetes and both processes have been related to the pathogenesis of diabetic kidney disease. Abstract : Chronic hyperglycaemia and inflammation are present in diabetes and both processes have been related to the pathogenesis of diabetic kidney disease. Epicatechin (EC) and main colonic phenolic acids derived from flavonoid intake, such as 2, 3-dihydroxybenzoic acid (DHBA), 3, 4-dihydroxyphenylacetic acid (DHPAA) and 3-hydroxyphenylpropionic acid (HPPA), have been suggested to exert beneficial effects in diabetes. This study was aimed at investigating whether the mentioned compounds could prevent inflammation in renal proximal tubular NRK-52E cells induced by high glucose and lipopolysaccharide (LPS). Pre-treatment of cells with EC and DHBA (5 μM) reverted the enhanced levels of pro-inflammatory cytokines, such as tumour necrosis factor-α (TNF-α), interleukin-6 (IL-6) and monocyte chemoattractant protein 1 (MCP-1), activated by high glucose and LPS. Additionally, EC and DHBA pre-incubation reduced the increased values of adhesion molecules, namely, intercellular cell adhesion molecule-1 (ICAM-1) and vascular cell adhesion molecule-1 (VCAM-1), as well as those of mitogen-activated protein kinases (MAPKs) [extracellular signal-regulated kinase (ERK), -c-jun N-terminal kinase (JNK) and -p38 protein kinase (p38)] activated by the high glucose and LPS challenge. Thus, in EC and DHBA pre-treated cells ICAM-1, p-ERK and p-JNK were returned to control values, and VCAM-1 and p-p38 levels were reduced by ∼20 and 25%, respectively, when compared to high glucose plus LPS-stimulated cells. Likewise, pre-treatment with EC and DHBA protected against high glucose plus LPS-triggered oxidative stress by preventing increased ROS and NADPH oxidase 4 (NOX-4) levels (∼25 and 45% reduction, respectively). By using specific inhibitors of p38 and NOX-4, the participation of both proteins in EC- and DHBA-mediated protection against inflammation and associated oxidative stress was shown. Taken together, EC and DHBA exert beneficial effects in renal proximal tubular cells, as they contribute to preventing the inflammatory-induced milieu and the accompanying redox imbalance, playing NOX-4/p38 a crucial role.